Application of the AMT Method to Gold Deposits: A Case Study in the Qinling Metallogenic Belt of North China Craton - Fengchun Li (MDPI AG, 2021)
The Lushi gold polymetallic ore-concentration area, located in the southern margin of North China Craton, is an important polymetallic ore district in the Qinling metallogenic belt. The Jianbeigou gold deposit is an important quartz vein type gold deposit in this district. In order to reveal the geological structure of the Jianbeigou gold deposit to guide deep prospecting, the EH4 conductivity image system was used in the Jianbeigou area. The sections obtained by the audio magnetotellurics method (AMT) indicate that the steeply dipping low resistivity zone in the area has a good corresponding relationship with the location of the known shallow ore bodies, and an extension in the deep. The low resistivity anomaly zone obtained by the inversion results are well correlated with the gold mineralization zone of the ore bodies, indicating good deep prospecting and exploration potential in this area. Based on geological and geophysical evidences, this paper inferred the possible occurrence location and depth range of the buried ore bodies. The AMT survey results reflect good exploration potential of the mining area and provide a geophysical basis for deep prospecting.